1996
DOI: 10.1007/s0021663540643
|View full text |Cite
|
Sign up to set email alerts
|

Metal body burdens and detoxifying enzymes in spiders from industrially polluted areas

Abstract: Detoxifying enzymes have been assayed and metal concentrations have been monitored in four species of spiders from differently contaminated localities in Southern Poland. A behavioural feeding activity and the life style decide on sensitivity and vulnerability of spiders. Wolf-spiders, more active than the web-spinners, cumulate higher amounts of metals, reflecting quantitatively and qualitatively the pollution level in their environment. Detoxifying systems in spiders appeared inducible and efficient to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Despite for manganese, the activity of the CarE and GST was negatively correlated with metal content in workers ( Table 2). Metals can inhibit the GST non-competitively, but may be activated by organic compounds, thus explaining higher activity in ants from more polluted sites as it was also depicted for spiders collected from Upper Silesia [38]. A tendency to the increase of CarE with the intensity of stressing factors (metals) in the food was confirmed for the Finnish ants, both in pupae and workers [20].…”
Section: Enzyme Patterns In Ants and Environmental Contaminationsupporting
confidence: 52%
See 1 more Smart Citation
“…Despite for manganese, the activity of the CarE and GST was negatively correlated with metal content in workers ( Table 2). Metals can inhibit the GST non-competitively, but may be activated by organic compounds, thus explaining higher activity in ants from more polluted sites as it was also depicted for spiders collected from Upper Silesia [38]. A tendency to the increase of CarE with the intensity of stressing factors (metals) in the food was confirmed for the Finnish ants, both in pupae and workers [20].…”
Section: Enzyme Patterns In Ants and Environmental Contaminationsupporting
confidence: 52%
“…A tendency to the increase of CarE with the intensity of stressing factors (metals) in the food was confirmed for the Finnish ants, both in pupae and workers [20]. Such compensatory mechanisms were not stated in other species of insects recently studied [3] but was also shown in web spinning spiders [38]. Increased level of herbivorous prey containing phenol compounds may also induce the activity of CarE both in spiders and in ants.…”
Section: Enzyme Patterns In Ants and Environmental Contaminationmentioning
confidence: 82%
“…Wolf spiders accumulate more heavy metals in their systems than do other ground-dwelling spider species because of their frequent hunting activities (Marczyk et al 1993;Rabitsch 1995;Wilczek and Migula 1996;Wilczek and Babczynska 2000). Previous laboratory (Jung et al 2005) and field (Jung et al 2007(Jung et al , 2008 experiments have suggested that the wolf spider, Pardosa astrigera L. Koch, is a potential bioaccumulator of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…, 2000; Roff, 2002). Physiological defence mechanisms such as increased metal excretion or the production of detoxifying enzymes (Wilczek & Migula, 1996) of tolerant genotypes (Maroni et al. , 1987; Van Straalen et al.…”
Section: Introductionmentioning
confidence: 99%